Disney's It's magic stories from the films - Strasser, Todd; Duke, Richard; Harchy, Philippe (New York : Disney Press, 1994)
Disney's animated fairies, wizards, and other magical characters--from Sleeping Beauty's fairy godmothers to Peter Pan and Tinker Bell--appear in their most magical moments.
Sleeping beauty (Sweet dreams to all ; The perfect party) -- Pinocchio (Little puppet made of pine ; Star light, star bright) -- The sword in the stone (Merlin's magic ; Brains over brawn) -- Aladdin (Visitors, at last! ; A stroke of genie-us!) -- Fantasia : The sorcerer's apprentice (Swept away ; Watery wizardry) -- Cinderella (What's a fairy godmother to do? ; Bibbidi-bobbidi-boo) -- Beauty and the beast (Waxing poetic ; Fit for a prince) -- The lion king (Rafiki knows ; A starry night) -- Peter Pan (Wouldn't you like to fly? ; Pixie dust and happy thoughts)
7 - 9 years
Keywords: Fairy tales; Children's stories; Children's poetry, American; Fairy tales; Folklore; Short stories; American poetry